Sociodemographic factors associated with food insecurity of a group of lactating women, Antioquia Colombia (2020)
ABSTRACT: Background: The scientific evidence is compelling in demonstrating the importance of breastfeeding on children's health, but for this process to be best achieved, the mother requires an adequate nutritional status, which is conditioned by the household's level of food security. In our context, research on the food and nutritional conditions of breastfeeding mothers is limited, which reflects the invisibility of this problem and the need to document it in order to strengthen public policies and nutritional care for this group. Objective: To assess the sociodemographic factors associated with food insecurity in a group of lactating women. Methods: Descriptive observational study of secondary sources, conducted from on the database of the Food and Nutrition Profile of the Department of Antioquia 2018-2019. The sociodemographic variables evaluated were area, socioeconomic level, age, educational level, occupation, household members, type of household, access to drinking water, health regime, household income and duration of breastfeeding. For the association between sociodemographic aspects and food security, the chi-square test of independence was applied. Results: Food insecurity was found in 78.6% of the lactating mothers, of which 36% presented moderate and severe insecurity with similar proportions. A significant association was found between food security and these sociodemographic variables: household members (p = 0.0011), socioeconomic level (p <0.001) with greater affectation at the lowest level. The mother's educational level (p = 0.008), household income (p = 0.006), the type of health affiliation (p = 0.011) and the type of family (p = 0.004) also presented significant association. Conclusions: Sociodemographic factors significantly impact food security in lactating women’s homes, which contributes to the limited access and availability of food in the home and prevents healthy eating adjusted to nutritional requirements during this stage. Lactating women’s nutrition should be prioritized because of its role in the reproductive cycle and in the health of children under two years of age.